2001
DOI: 10.1021/ed078p194
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Is Learning—Maximum Incentive, Minimum Discipline in Student Groups Teaching General Chemistry

Abstract: The idea of using students or groups of students to lead a discussion is nothing new in chemistry classes or other academic fields (1-5). A sustained effort to actively engage students in lecture classes has been going on in the sciences for at least a decade (6-11), with pros and cons about such teaching being voiced by both faculty and students (12)(13)(14). I wish to report on a student group teaching technique that has been used successfully in the general chemistry lecture at the 100-level. This technique… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Group work may not be as easy or robust in large classes unless the instructor takes purposeful steps to initiate and sustain them . Articles published in this Journal show that, regardless of class size, many educators have recognized the value of group work and are using creative ways to implement them. …”
Section: Adaptabilitymentioning
confidence: 99%
“…Group work may not be as easy or robust in large classes unless the instructor takes purposeful steps to initiate and sustain them . Articles published in this Journal show that, regardless of class size, many educators have recognized the value of group work and are using creative ways to implement them. …”
Section: Adaptabilitymentioning
confidence: 99%
“…It has been used in general chemistry courses to aid student centered learning, and to increase student engagement . Benvento reports on using peer learning in assigned groups to facilitate building relationships between students so that they are more likely to help one another both in and out of class . More recently, Williams et al have shown how peer learning in a laboratory setting leads to “enduring understanding” .…”
Section: Literature Backgroundmentioning
confidence: 99%
“…This indicates that a more self-defined mastery of material from the student perspective led to greater achievement. Benvenuto (2001) also assessed this structure using a "maximum incentive, minimum discipline" model in a chemistry course and looked at a reward-heavy objective for good work, as assessed by their peers, without the fear of a punitive grade for poor work. Although students generally favored this method of incentive and peer-evaluation, final assessment revealed students did desire some form of punishment for those who did not contribute good work (Benvenuto, 2001).…”
Section: Student-centered Learningmentioning
confidence: 99%
“…Benvenuto (2001) also assessed this structure using a "maximum incentive, minimum discipline" model in a chemistry course and looked at a reward-heavy objective for good work, as assessed by their peers, without the fear of a punitive grade for poor work. Although students generally favored this method of incentive and peer-evaluation, final assessment revealed students did desire some form of punishment for those who did not contribute good work (Benvenuto, 2001). Although the literature may appear contradictory at times, it seems as though the use of incentives could be fruitful when the teaching method balances with self-and peer-defined expectations by the students, and those students have a high intrinsic motivation to learn.…”
Section: Student-centered Learningmentioning
confidence: 99%